Depicting life, analysing the power: The 'actuality' of Italian cinema. Issue 2 (1st June 2014) - Tagliani, Giacomo
The increasing production of biographical films dealing with power and its figures raises interesting questions about the nature and the aims of political cinema. What are the strategies used to represent people whose public image has completely overlapped to their identity? This matter concerns not only thematic aspects of the biopic genre, but more in depth it discloses fundamental issues at the basis of any theory of cinema. From this point of view, some Italian instances propose original solutions, creating a coherent framework in continuity with a long tradition that has marked the history of Italian thought. This article aims at making a survey of these inputs through the analysis of contemporary relevant texts – above all Il Caimano/The Caiman (Moretti, 2006), Il Divo: La spettacolare vita di Giulio Andreotti/Il Divo (Sorrentino, 2008), Vincere/To Win (Bellocchio, 2009) – in the attempt of defining the space of effectiveness of this new line of development within the huge field of political cinema.